(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
This essay aims at delving into the issues raised by the recent governmental guidelines on medically assisted reproduction, taking into account Law No. 40 of 2004, the judgments of the Italian Constitutional Court and the development of technical and scientific knowledge in this matter.